Deep Electron and Hole Traps in Electron-Irradiated Green GaN/InGaN Light Emitting Diodes. (5th October 2017) - Lee, In-Hwan; Polyakov, A. Y.; Smirnov, N. B.; Shchemerov, I. V.; Chung, Tae-Hoon; Lagov, P. B.; Zinov'ev, R. A.; Pearton, S. J.
Abstract : Deep electron and hole trap spectra and electroluminescence (EL) efficiency of green multi-quantum-well (MQW) GaN/InGaN light emitting diodes were measured before and after 6 MeV electron irradiation. Starting with a fluence of 5 × 10 15 cm −2, electron irradiation increased the concentration of existing electron traps with levels at Ec −0.5 eV and introduced new electron traps with levels near Ec −1 eV. The latter are the well known radiation defects formed in the GaN barriers of the GaN/InGaN MQW region. The degradation of the EL efficiency after irradiation correlates with changes of the Ec −0.5 eV and Ec −1 eV electron trap density, suggesting these are effective non-radiative recombination centers. By sharp contrast, the concentration of the dominant hole traps with levels near Ev +0.45 eV decreased after, which eliminates these from the role of Shockley-Read-Hall defects actively participating in recombination.